THE SIGNIFICANCE OF WRESTLING SPORTS FOR SOCIETY AND THE HISTORY OF ITS FORMATION - Sharipov Habibullo Abdukahharovich (Journals Park Publishing, 2022)
This article talks about the importance of wrestling for society and the history of its formation. A society with increased attention to sports develops in the style of a healthy society. There are all types of sports, which serve not only physical fitness, but also spiritual development of a person. In particular, wrestling is a defense of national values and it ensures the strengthening of national pride and confidence in a bright future.
Keywords: wrestling, sport, society, art of fighting, national wrestling, athlete, national values, healthy society.